Socioeconomic Inequalities in Child Health in Ireland - LAYTE, RICHARD; NOLAN, ANNE (ESRI, 2013)
There is extensive empirical evidence on the link between socio-economic status (SES) and child health outcomes. However, there is some international evidence that the SES gradient in child health is weaker for objective indicators of child health (e.g., anthropometric measures such as height) than for subjective indicators (e.g., parental assessments of general health status). In this paper, we use detailed cross-sectional micro-data on two cohorts of children in Ireland (aged 9 months and 9 years) to examine the SES gradient in various indicators of child health (length/height; weight/BMI; general health status; chronic illness incidence). Using two main indicators of SES, namely household income and mother?s highest level of education, we find only limited support for the contention that the SES gradient in child health in Ireland is stronger for more subjective measures of child health.
PUBLISHED
Keywords: Socio-Economic Health; Child Health; Inequalities; Ireland